2011
DOI: 10.1007/s00296-010-1722-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Saccharomyces cerevisiae (ASCA) and anti-endomysial antibodies in spondyloarthritis

Abstract: Spondyloarthritis (SpA) are diseases with increased gut inflammation. To search for (anti-Saccharomyces cerevisiae) ASCA IgA, ASCA IgG, and anti-endomysial antibodies (EmA-IgA) in a cohort of 70 patients with SpA, we found 18.6% (13/70) positive for IgA-ASCA in the SpA group and 3/57 (5.2%) in the control group (P = 0.031). ASCA IgG and EmA-IgA were found at the same frequency in SpA and controls. No relationship of ASCA IgA positivity could be established with disease activity (measured by ESR, C-reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Several recent studies have shed light on the spectrum of noninflammatory bowel diseases demonstrating ASCA phenomenon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). ASCA do precede Crohn's disease development in as many as one-third of individuals, but the positive predictive value of the test becomes of relevant issue and clinicians using ASCA in the evaluation of inflammatory bowel disease should be aware of this (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shed light on the spectrum of noninflammatory bowel diseases demonstrating ASCA phenomenon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). ASCA do precede Crohn's disease development in as many as one-third of individuals, but the positive predictive value of the test becomes of relevant issue and clinicians using ASCA in the evaluation of inflammatory bowel disease should be aware of this (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that ASCA had a highpredictive value for inflammatory bowel disease (4). Additionally, elevated levels of ASCA had also been found in patients with Behcet's disease (5), spondyloarthritis (6), celiac disease (CD) (7,8), intestinal tuberculosis (9), primary biliary cirrhosis (10,11), autoimmune hepatitis (12), type 1 diabetes (13), and systemic lupus erythematosus (14,15).…”
Section: Introductionmentioning
confidence: 96%
“…The development of arthritis in these patients probably involves genetic and environmental components, which turn patients susceptible to luminal microbiota that triggers the arthritis [8]. In our region, Andretta et al [23] studying 70 patients with SpA described an increase of the IgA-ASCA (anti- Saccharomyces cerevisiae antibody) positivity, suggesting that this group could have a greater intestinal permeability. However, these authors could not demonstrate any relationship of IgA ASCA with disease activity, functional index or clinical profile.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that intestinal IL-23 plays a pivotal role in the pathogenesis of β-glucan-induced SpA pathogenesis in SKG mice [12] . In humans, anti-Saccharomyces cerevisiae antibodies (ASCAs) are detected in Crohn's disease patients and in AS patients [13][14][15]. The importance of the IL-23-IL-17 axis has been emphasised also in human SpA pathogenesis [16].…”
Section: Introductionmentioning
confidence: 99%